Evaluasi Penambahan Pembangkit Baru 0,5 MWp Terhadap Profil Tegangan Pada Sistem Distribusi Singosari - Ahmad Iqbal Zajuli; Irrine Budi Sulistiawati; Awan Uji Krismanto (Universitas Darul Ulum, 2022)
The development of renewable energy in Indonesia has grown quite rapidly, one of which is PLTS. With this new power plant, it is hoped that the excessive use of fossil fuels will be reduced. in 2021 there a new PLTS operating in one of the universities, i.e at the Malang National Institute of Technology with a capacity of 0.5 MWp. The PLTS works on-grid into the Singosari distribution system through the Karangploso feeder so that the addition of a new generator of 0.5 MWp can cause changes in the voltage profile. the voltage profile itself is the voltage condition to be at the nominal voltage either when there is a change in load conditions or when power losses occur in the line with a standard allowable voltage profile of 0.95>V> 1.05 pu. The study used in this research is a power flow study with the Newton-Raphson method. This method is used to calculate the voltage profile on each bus of the power system either during the base case condition or when the system is integrated with PLTS 0.5 MWp. so that with the addition of a new power plant with a capacity of 0.5 MWp, it is necessary to evaluate the addition of a new generator with a capacity of 0.5 MWp to the voltage profile in the Singosari distribution system through the Karangploso feeder.